The year people helped zebras to stand up: Climatic variability and extreme weather observed and portrayed by Kenyan Maasai pastoralists - Roque de Pinho, J. (Changing climate, changing worlds: Local knowledge and the challenges of social and ecological change, 2020)
In 2009, an extreme drought devastated herds of livestock and wildlife across southern Kenya and impacted local livelihoods. For local Maasai pastoralists, this event was both unprecedented and perceived as part of a trend in increasing climatic instability. In this chapter, I contextualize Maasai pastoralists’ experiences of this extreme drought by examining their climatological and meteorological knowledge, and how it informed their interpretations of the drought. Based on mixed-methods research, including visual ethnography, I first examine Maasai perceptions of recent and current climatic conditions in Kajiado and Narok counties, and their weather forecasting expertise (which includes observation of fauna and flora). Second, I explore Maasai observations of biodiversity changes associated with climatic changes. I do so by analyzing images of unusual animal behavior photographed during the 2009 drought by Maasai agropastoralists who acted as collaborative researchers and photographers. Across both counties and over a decade, perceptions of evolving climatic variability feature longer dry seasons, more intense rains and droughts, altered spatial and temporal rainfall patterns, and the notion that traditional forecasting knowledge is increasingly irrelevant as weather events and indicators are no longer synchronized. The 2009 drought was not predicted and, as my collaborators documented in photography, caused animals to behave strangely and in unprecedented ways, e.g., letting themselves be touched by people, entering settlements, and dying of starvation. This participatory visual research project resulted in unexpectedly rich, fine-grained information on local drought impacts and on human and nonhuman coping, which was later shared with the community and local policy-makers. Importantly, the participatory process fostered critical debate on future livelihood options under climate change among the project participants and their local audience.